Introducing visible-light sensitivity into photocatalytic CeO2 nanoparticles by hybrid particle preparation exploiting plasmonic properties of gold: enhanced photoelectrocatalysis exemplified for hydrogen peroxide sensing. Issue 2 (24th December 2020) - Zhao, Shuang; Riedel, Marc; Patarroyo, Javier; Bastus, Neus; Puntes, Victor; Yue, Zhao; Lisdat, Fred; Parak, Wolfgang J.
Abstract : Enhancement of the photocatalytic current of CeO2 NPs upon their linkage to plasmonic Au NPs. Abstract : In this report we combine the catalytic properties of CeO2 nanoparticles with their transduction ability for photoelectrochemical sensing. This study highlights the usage of CeO2 providing catalytic activity towards H2 O2, but only with a limited excitation range in the UV for the construction of a sensing system. In order to improve the photoelectrocatalysis of CeO2 nanoparticles by extending their excitation to visible light, Au/CeO2 core/shell hybrid nanoparticles have been synthesized. The hybrid nanoparticles are fixed on electrodes, allowing for the generation of photocurrents, the direction of which can be controlled by the electrode potential (without bias). The application of the hybrid nanoparticles results in an enhanced photocurrent amplitude under white light illumination as compared to the pure CeO2 nanoparticles. Wavelength-dependent measurements confirm the participation of the Au core in the signal transduction. This can be explained by improved charge carrier generation within the hybrid particles. Thus, by using a plasmonic element the photoelectochemical response of a catalytic nanoparticle ( i.e. CeO2 ) has been spectrally extended. The effect can be exploited for sensorial hydrogen peroxide detection. Here higher photocatalytic current responses have been found for the hybrid particles fixed to gold electrodes although the catalytic reduction has been comparable for both types of nanoparticles. Thus, it can be demonstrated that Au/CeO2 core–shell nanoparticles allow the utilization of visible light for photoelectrochemical hydrogen peroxide (H2 O2 ) detection with improved sensitivity under white light illumination or application of such particles with only visible light excitation, which is not possible for pure CeO2 . With help of the layer-by-layer (LbL) technique for nanoparticle immobilization, the electrode response can be adjusted and with a 5 layers electrode a low detection limit of about 3 μM H2 O2 with a linear detection range up to 2000 μM is obtained.